The relationship between nutrient intake, lifestyle, and non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus: Results from the National Health and Nutrition Examination Surveys 2007–2018 - Sun, Liangyuanhui; He, Zhiqing; Li, Yanbin; Huo, Zijun; Liu, Liehua (Clinical nutrition ESPEN, 2025)
More than half of the individuals with type 2 diabetes mellitus (T2DM) are accompanied by Non-alcoholic fatty liver disease (NAFLD). This study aimed to explore the relationship between nutrient intake, lifestyle, and the risk NAFLD in patients with T2DM. This study comprised 2110 adult patients with diabetes from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. We employed weighted logistic regression to assess the associations between nutrient intake, lifestyle and NAFLD, while exploring potential non-linear relationships using restrictive cubic spline analysis. Additionally, we validated our findings through subgroup analyses and sensitivity analyses to ensure the robustness and reliability of our results. Out of 2110 diabetes patients, 1743 were diagnosed with NAFLD, and 53.43 % of them were male. After adjusting for potential confounders, we found a negative correlation between Vitamin K intake and the occurrence of NAFLD in patients with T2DM (OR = 0.885 [0.829, 0.959]). This dose–response relationship was further validated through stratification analysis by tertiles of vitamin K intake. Lycopene intake is identified as a risk factor for NAFLD in patients with T2DM. Specifically, for every 100 μg of lycopene ingested, there was a 0.2 % higher likelihood of NAFLD (OR = 1.002 [1.0001, 1.005], p < 0.05). Conversely, a 0.5 % reduction in NAFLD risk was observed with the same amount of lutein intake (OR = 0.995 [0.992, 0.999], p < 0.05). Furthermore, we also found that a high-quality diet can reduce the risk of NAFLD in patients with T2DM, with an odds ratio of 0.208 (0.101, 0.430). Increasing intake of Vitamin K and lutein, reducing intake of lycopene, and improving dietary quality may lower the risk of NAFLD in patients with T2DM.